Panduan kesehatan menurunkan berat badan - Chasanah, Siti Amanatun (Maliki Interdisciplinary Journal, 2025)
Sustainable and healthy weight loss requires a holistic approach that combines balanced nutrition, regular physical activity, and lifestyle changes that support overall well-being. This article reviews expert advice from nutritionists and fitness trainers on effective strategies for weight loss. It discusses setting realistic goals, the importance of consuming a balanced diet in appropriate portions, and the types of exercise that support weight loss. Additionally, it emphasizes necessary lifestyle changes, such as adequate sleep, stress management, and proper hydration. By following these guidelines, individuals can achieve weight loss in a healthy, measurable, and sustainable way.